The therapeutic mechanism of Compound Lurong Jiangu Capsule for the treatment of cadmium-induced osteoporosis: network pharmacology and experimental verification - Zhou, Ya-shuang; Huang, Jian; Cao, Wen-xuan; Yu, Ao-xue; Li, Pan; Liang, Jin-ling; Leng, Xiang-yang; Jin, Jian; Yu, Peng; Liu, Jia (Frontiers in Endocrinology, 2024)
Background. Among bone diseases, osteoporosis-like skeleton, such as trabecular thinning, fracture and so on, is the main pathological change of cadmium-induced osteoporosis(Cd-OP), accompanied by brittle bone and increased fracture rate. However, the mechanism underlying cadmium-induced osteoporosis has remained elusive. Compound Lurong Jiangu Capsule (CLJC) is an experienced formula for the treatment of bone diseases, which has the effect of tonifying kidney and strengthening bones, promoting blood circulation and relieving pain. Objective. Network pharmacology and molecular docking technology combined with experiments were used to investigate the potential mechanism of CLJC in treating Cd-OP. Method. The active compounds and corresponding targets of each herb in CLJC were searched in the TCMSP and BATMAN-TCM databases. The DisGeNet, OMIM, and GeneCards databases searched for Cd-OP targets.The relationship between both of them was visualized by establishing an herb-compound-target network using Cytoscape 3.9.1 software. Gene ontology (GO), and Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analyses were performed after determining the intersection of the targets from CLJC and Cd-OP. What's more, molecular docking was performed to validate the results. All of them were aim to obtain hud signaling pathways for further study. Finally, BAX, BCL-2, and CASPASE-3 were screened and selected for further experiments, which included bone imaging and reconstruction analysis (Micro-CT), hematoxylin-eosin Staining (HE), and western blot (WB). Results.106 common targets from CLJC and Cd-OP targets were identified. KEGG pathway analysis suggested that multiple signaling pathways, such as the pathways in cancer, may play roles in treatment. Verification of the molecular docking was successful. Here we showed that Cd-OP displayed Tb.Th and Tb.N significantly reduced and even broke, irregular proliferation of bone cortex, uneven and loose trabecular bone arrangement, changed in apoptosis-related proteins, such as significant upregulation of CASPASE-3, BAX protein and significant downregulation of BCL-2 protein in vivo, while CLJC rescued these phenotypes. Conclusion.This study revealed that CLJC can reduce the expression of apoptosis-related proteins, and multiple components and multiple targets inhibit Cd-OP through apoptosis signaling pathway.